Foreign aid, public investment, and the informal economy. (18th July 2021) - Chatterjee, Santanu; Kelly, Mark C.; Turnovsky, Stephen J.
Abstract: This paper examines the absorption of foreign aid in the presence of formal and informal production. Calibrating a two‐sector open economy model to 67 aid‐recipient countries for 1990–2019, we show that an increase in foreign aid drives resources into the informal sector, and away from the formal sector. With untied aid, the expansion of the informal sector can lead to an economic contraction through the Dutch Disease effect. An economic expansion with an increase in the share of formal production can be attained by re‐allocating existing aid to public investment rather than an increase in the aggregate level of aid.